OKRA FRUIT GUM-CHITOSAN IMPREGNATED POLYMER NETWORK FILMS: FORMULATION AND SUBSTANTIAL DEPICTION - Nagpal, Meenu; Aggarwal, Geeta; Jain, Upendra Kumar; Madan, Jitender (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present research is aimed at formulation and evaluation of okra fruit gum (OFG)-chitosan (CH) impregnated polymer network films. Methods: The film forming property of the gum attained from fruits of Abelmoschus esculentus was enhanced by co-processing it with CH. Estimation of properties including swelling index (SI), film volume, volume index, film surface contact angle with buffer solutions (pH 1.2, 7.4 or 6.8), work of adhesion (Wa), and spreading coefficient was done. Results: The contact angle and SI of OFG-CH film in both acidic and alkaline buffers were witnessed to be lowest when equated with the films prepared with difference in ratios of both gum and CH. Moreover, the Wa and spreading coefficient were less for this film. These results could be attributed to the optimum interaction between –COO− groups of gum and -NH3+ groups of CH. Conclusion: The actual nature of the film found to be tough, flexible, and water resistant. Hence, the results have shown that the films produced have a high potential for use in modified drug release and in food and pharmaceuticals.